Clopidogrel combined with rivaroxaban in peripheral artery disease after revascularization - Lu, Min; Li, Jiaqi; Ni, Huanyu; Qiao, Tong; Wang, Baoyan (Frontiers in Pharmacology, 2025)
BackgroundTo evaluate the efficacy and safety of clopidogrel-rivaroxaban combination compared to aspirin-rivaroxaban combination in patients with symptomatic peripheral artery disease (PAD).MethodsConsecutive patients with symptomatic PAD patients were analyzed from January, 2018 to June, 2022 at Nanjing Drum Tower Hospital. Patients were divided into two groups based on the antithrombotic therapy. The primary efficacy outcome was a composite of major adverse cardiovascular events (MACE) and major adverse limb events (MALE), and the primary safety outcome was major bleeding. Patients were followed until the first occurrence of any outcomes or the study end date (30 June 2024).ResultsA total of 695 patients were enrolled into this study. The clopidogrel-rivaroxaban combination significantly reduced the risk of composite outcome (HR: 0.59, 95%CI: 0.41–0.83) without increasing the risk of major bleeding (HR: 0.68, 95%CI: 0.27–1.69). When analyzed separately, clopidogrel-rivaroxaban combination was associated with a reduced risk of MALE (HR: 0.61, 95%CI: 0.41–0.91), although no significant differences were observed in terms of MACE (HR: 0.64, 95%CI: 0.34–1.20) or all bleeding events (HR: 1.00, 95%CI: 0.52–1.93). In the subgroup analysis, there were no significant interactions between the treatment groups and the subgroups of age, diabetes, lesion sites, Rutherford classifications and renal function for composite outcome, MACE and MALE.ConclusionThe clopidogrel-rivaroxaban combination in PAD patients may offer enhanced cardiovascular protection without increasing the risk of bleeding complications. These findings suggested that clopidogrel could be a superior alternative to aspirin in dual antithrombotic therapy for PAD management.